CCCTC-Binding Factor Locks Premature IgH Germline Transcription and Restrains Class Switch Recombination - Marina-Zárate, Ester; Pérez-García, Arantxa; Ramiro, Almudena R. (Frontiers in Immunology, 2017)
In response to antigenic stimulation B cells undergo Class Switch Recombination (CSR) at the immunoglobulin heavy chain (IgH) to replace the primary IgM/IgD isotypes by IgG, IgE or IgA. CSR is initiated by activation-induced cytidine deaminase (AID) through the deamination of cytosine residues at the switch (S) regions of IgH. B cell stimulation promotes germline transcription (GLT) of specific S regions, a necessary event prior to CSR because it facilitates AID access to S regions. Here we show that CCCTC-binding factor (CTCF) deficient mice are severely impaired in the generation of germinal center B cells and plasma cells after immunization in vivo, most likely due to impaired cell survival. Importantly, we find that CTCF deficient B cells have an increased rate of CSR under a variety of stimulation conditions in vitro. This effect is not secondary to altered cell proliferation or AID expression in CTCF deficient cells. Instead, we find that CTCF deficient B cells harbour an increased mutation frequency at switch regions, probably reflecting an increased accessibility of AID to IgH in the absence of CTCF. Moreover, CTCF deficiency triggers premature GLT of S regions in naïve B cells. Our results indicate that CTCF restricts CSR by enforcing GLT silencing and limiting AID access to IgH.